The determinants of inflation in three selected countries / Nurfarah Diyana Khairul Azman and Farah Eizlin Ilyana Mazli - Khairul Azman, Nurfarah Diyana (Faculty of Business and Management, 2019)
Inflation targeting has been widely adopted in economics of both developed and developing countries. It could also happen towards the third world country. Therefore, many studies have been made to investigate the variables that will affect the inflation in a country. Considering some variables which have affected the inflation, this study tried to investigate the relationship between exchange rate, government expenditure, interest rate and unemployment rate with inflation in three selected countries which are Japan, Malaysia and Malawi by using the annual data from 1991 to 2016. To achieve the objectives of the study, Pooled OLS model has been used to assess the relationship between real unemployment rate and inflation. The results of the study demonstrated that there was a negative significant relationship between inflation and unemployment rate. In addition, it was shown that government expenditure had a significant and negative effect on inflation.